PERBEDAAN SALINITAS MEDIA TERHADAP EFISIENSI PEMANFAATAN PAKAN BENIH IKAN NILA GIFT (Oreochromis sp) - Silvia Rosdianasari, M.B; Syakirin .; Komariyah . (LPPM Universitas Pekalongan, 2013)
This study aimed to determine the effect of the differences and optimal salinity levels on the efficiency of feed utilization in Oreochromis sp. Method used in this study is the experimental laboratory methods. Research carried out by completely randomized design with 4 treatments and 3 replications. The treatment includes a treatment with 0 ppt salinity, Treatment B: 5 ppt, Treatment C: 10 ppt, Treatment D: 15 ppt.Differences in the low salinity culture media failed to give a positive response to the efficiency of feed utilization of fish seed is cultivated. Decreasing salinity is used, it will affect the efficiency of feed utilization of tilapia seed. In the C treatment (10 ppt salinity) gives the maximum response to the efficiency of feed utilization Oreochromis sp. which, at 85.95% followed by treatment D (74.26%), treatment B (58.68%) and treatment A (48.49%). Treatment differences in salinity media on the efficiency of feed utilization Oreochromis s. produces a quadratic curve with equation Y = 45.69 + 5.37 X - 0.22 X2. Water quality of the media during the study the water temperature is 25 - 28oC, pH 7.3, and DO from 4.5 to 5.6 ppm, so it is still within the range appropriate for the survival of Oreochromis sp. Keywords: salinity, the efficiency of feed utilization